Yoga-plus exercise mix promotes cognitive, affective, and physical functions in elderly people. (2nd November 2019) - Hishikawa, Nozomi; Takahashi, Yoriko; Fukui, Yusuke; Tokuchi, Ryo; Furusawa, Junichi; Takemoto, Mami; Sato, Kota; Yamashita, Toru; Ohta, Yasuyuki; Abe, Koji
ABSTRACT: Objectives : Increased attention is being paid to Asian medicine in balanced total health care. We investigated the effects of mixed exercise including yoga ('Yoga-plus') among elderly individuals. Methods : A total of 385 subjects (72 males and 313 females, 75.5 ± 8.7 years old) participated in a 12-month (M) exercise program at a health and welfare center, a day service center, and a nursing home. Cognitive, affective, and physical functions, and activities of daily living (ADL), were compared at baseline (0M), 6M and 12M of exercise intervention. Results : Mean scores on the frontal assessment battery, clock drawing test, cube copying test, letter fluency, and category fluency significantly improved after the Yoga-plus intervention, while mini-mental state examination, Hasegawa dementia score-revised, and trail-making test performance were relatively stable. Affective scores on the geriatric depression scale (GDS), apathy scale (AS) and Abe's behavioral and psychological symptoms of dementia were not significantly affected by exercise therapy, but subgroups with higher baseline GDS (GDS ≥ 5) and AS (AS ≥ 16) scores showed a significant improvement after intervention. One-leg standing time and 3-m timed up and go test performance significantly improved after 12M intervention. Discussion : Yoga-plus improved cognitive, affective, ADL, and physical functions in a local elderly population, particularly among below-baseline individuals, indicating the benefits of dementia prevention among elderly individuals.